Intra-Household Redistribution of Income and Calorie Consumption in South-Western Nigeria - Adebayo B. Aromolaran (Yale University, Economic Growth Center, 2004)
This study investigates how per capita calorie intake in low income households of rural southwestern Nigeria responds to changes in total household income and women's share of household income. The study addresses two major questions. First, is calorie-income elasticity large enough to justify the use of income increases as a food/nutrition policy strategy for increasing calorie intake among low income households? Second, what is the potential effect of intra-household redistribution of income from men to women on per capita calorie consumption? My results show that calorie-income elasticity is small and close to zero, implying that income policies may not be the most effective way to achieve substantial improvements in calorie consumption. I also find that increases in women's share of household income are likely to result in marginal declines in per capita food calorie intake, suggesting that income redistribution from men to women would not increase per capita food energy intake in these households.
Keywords: D13; I12; O15; Q18; 330; Nigeria; Intra-Household Redistribution of Income; Women's Income Share Elasticity; Income Elasticity; Calorie Consumption; Haushaltseinkommen; Intergenerationale Übertragung; Nahrungsmittelkonsum; Fraueneinkommen; Nigeria (Südwest)